Whole-genome sequencing of extrachromosomal circular DNA of cerebrospinal fluid of medulloblastoma - Zhu, Yi; Liu, Zhihui; Guo, Yuduo; Li, Shenglun; Qu, Yanming; Dai, Lin; Chen, Yujia; Ning, Weihai; Zhang, Hongwei; Ma, Lixin (Frontiers in Oncology, 2022)
Background: Medulloblastoma (MB) is a malignant tumor associated with a poor prognosis in part due to a lack of effective detection methods. Extrachromosomal circular DNA (eccDNA) has been associated with multiple tumors. Nonetheless, little is currently known on eccDNA in MB. Methods: Genomic features of eccDNAs were identified in MB tissues and matched cerebrospinal fluid (CSF) and compared with corresponding normal samples using Circle-map. The nucleotides on both sides of the eccDNAs breakpoint were analyzed to understand the mechanisms of eccDNAs formation. Bioinformatics analysis combined with the Gene Expression Omnibus (GEO) database identified features of eccDNA-related genes in MB. Lasso Cox regression model, univariate and multivariate Cox regression analysis, time-dependent ROC, and Kaplan–Meier curve were used to assess the potential diagnostic and prognostic value of the hub genes. Results: EccDNA was profiled in matched tumor and CSF samples from MB patients and control, eccDNA-related genes enriched in MB were identified. The distribution of eccDNAs in the genome was closely related to gene density and the mechanism of eccDNA formation was evaluated. EccDNAs in CSF exhibited similar distribution with matched MB tissues but were differentially expressed between tumor and normal. Ten hub genes prominent in both eccDNA dataset and GEO database were selected to classify MB patients to either high or low risk groups, and a prognostic nomogram was thus established. Conclusions: This study provides preliminary evidence of the characteristics and formation mechanism of eccDNAs in MB and CSF. Importantly, eccDNA-associated hub genes in CSF could be used as diagnostic and prognostic biomarkers for MB.